2006
DOI: 10.1002/crat.200610730
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrical conduction of Sb2O3 thin films

Abstract: Antimony trioxide (Sb 2 O 3 ) thin films have been deposited onto glass substrates using thermal evaporation technique at room temperature. The structural feature and surface morphology were characterized by transmission electron microscopy (TEM) and scanning electron microscopy (SEM). Sandwich-type structures were deposited with films thickness d = 0.55 µm using evaporated electrodes of silver. Current-voltage (J-U) characteristics have been measured at various fixed temperatures in the range 293-473 K. In al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The focus of previous studies for Sb 2 O 3 has been the electrical, vibrational and optical properties [6,7,27,28,29]. Optical band gaps in the range of 3.40-4.00 eV have been reported for Sb 2 O 3 , with the indirect/direct nature of the band gap unclear [6,7,28]. Hartree-fock calculations were used to characterise the electronic density of the Sb 4 O 6 clusters in the Senarmontite structure, indicating the presence of lone pairs on the Sb cations [30].…”
Section: Introductionmentioning
confidence: 99%
“…The focus of previous studies for Sb 2 O 3 has been the electrical, vibrational and optical properties [6,7,27,28,29]. Optical band gaps in the range of 3.40-4.00 eV have been reported for Sb 2 O 3 , with the indirect/direct nature of the band gap unclear [6,7,28]. Hartree-fock calculations were used to characterise the electronic density of the Sb 4 O 6 clusters in the Senarmontite structure, indicating the presence of lone pairs on the Sb cations [30].…”
Section: Introductionmentioning
confidence: 99%
“…They also used density of states analysis to show that the presence of asymmetric density correlated with the amount of mixing between the cation p states and the antibonding cation s–O p interaction at the top of the valence band. Other studies of α-Sb 2 O 3 have focused on its structural and electrical properties and its characterization with Raman spectroscopy. , Similarly, the majority of the previous studies on the mixed valence oxide, Sb 2 O 4 , have also typically focused on the structure/Raman spectra. , Due to its use as a mixed-oxide catalyst, there has been additional study of the defect chemistry associated with dopants in Sb 2 O 4 . For example, Moore and Widatallah reported that the dominant intrinsic defect in the low temperature α-form is an oxygen Frenkel and that the incorporation of Fe III into the structure occurs via substitution with Sb III ions .…”
Section: Introductionmentioning
confidence: 99%
“…The measurement results of Hall effect (Table S1, Supporting Information) show that the majority carriers of Si are holes, and the majority carriers of Sb 2 O 3 are electrons. [37,38] And the Fermi energy level of PdTe 2 is between the Fermi energy levels of Sb 2 O 3 and p-type Si (Figure S1b,c, Supporting Information). The introduction of PdTe 2 in Sb 2 O 3 /Si heterojunction constructs the Sb 2 O 3 /PdTe 2 /Si heterojunction structure.…”
Section: Working Mechanism Of Sb 2 O 3 /Pdte 2 /Si Heterojunctionmentioning
confidence: 99%